2022
DOI: 10.1186/s12951-022-01655-8
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-140-5p inhibits osteogenesis by targeting IGF1R and regulating the mTOR pathway in ossification of the posterior longitudinal ligament

Abstract: Background Ossification of the posterior longitudinal ligament (OPLL) is a disabling disease whose pathogenesis is still unclear, and there are no effective cures or prevention methods. Exosomal miRNA plays an important role in the osteogenesis of ectopic bone. Therefore, we focused on the downregulation of miR-140-5p in OPLL cell-derived exosomes to explore the mechanism by which exosomal miR-140-5p inhibits osteogenesis in OPLL. Results Exosomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Some research has proposed using ligament cells derived from OPLL to create scaffolds by placing them on the surface of a demineralized bone matrix, which is then implanted subcutaneously in nude mice to induce heterotopic ossification. 10 , 63 However, this animal model using nude mice cannot fully reflect the ossification’s pathological process, as inflammation is a significant factor in physiological and pathological ossification, as evidenced by our sequencing data and previous research. 64 To overcome these limitations, we used commercially available rhBMP-2 biomaterials subcutaneously implanted into C57BL/6 mice to establish an ossification model (BIO), which we used to evaluate sorafenib’s effectiveness in inhibiting ossification in both BIO and LSO models.…”
Section: Discussionmentioning
confidence: 81%
“…Some research has proposed using ligament cells derived from OPLL to create scaffolds by placing them on the surface of a demineralized bone matrix, which is then implanted subcutaneously in nude mice to induce heterotopic ossification. 10 , 63 However, this animal model using nude mice cannot fully reflect the ossification’s pathological process, as inflammation is a significant factor in physiological and pathological ossification, as evidenced by our sequencing data and previous research. 64 To overcome these limitations, we used commercially available rhBMP-2 biomaterials subcutaneously implanted into C57BL/6 mice to establish an ossification model (BIO), which we used to evaluate sorafenib’s effectiveness in inhibiting ossification in both BIO and LSO models.…”
Section: Discussionmentioning
confidence: 81%
“…Notably, the Pi3k/Akt pathway is vital for facilitating osteoblast differentiation and represents a major mechanism promoting bone formation through various natural compounds, including microRNA, exosomes, and filipin/hydroxyapatite [ [34] , [35] , [36] ]. Similarly, we suggest that the Pi3k/Akt signaling pathway is a key contributor to osteogenic differentiation promoted by the Zn-0.8 Mg alloy extract following the longer period of induction (14 days).…”
Section: Resultsmentioning
confidence: 99%
“…[ 34 ] It was found that miRNAs (from MSCs‐derived sEVs) could be delivered to recipient cells and regulate downstream pathways. [ 35 ] Those miRNAs in MT‐EVs that may participate in therapeutic actions, have never been investigated and verified. In this study, we performed miRNA sequencing of MT‐EVs, and compared their expression levels with those of NC‐EVs.…”
Section: Discussionmentioning
confidence: 99%